Mathematical Literacy Skills of Students in the Digital Era: Implementation of Reciprocal Teaching and Digital Literacy - Suri, Fraulein Intan; Farida, Farida; Fauziah, Alvyyatun; Pradana, Kenny Candra (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
In reality, the level of mathematical literacy among students remains relatively low. On the other hand, although digital tools have significant potential to enhance the effectiveness of learning, their application in the educational process is still limited, compounded by the low level of students' digital literacy, which further hinders the optimal use of technology in mathematical learning. Based on these issues, the aim of this study is to determine the effect of the reciprocal teaching model and digital literacy on students' mathematical literacy skills. The population of this study consists of X AKL students at SMK N 1 Kalianda. The sample includes classes X AKL 1 and X AKL 2. This research is a quasi-experimental study with a 2 × 3 factorial design. The data collection techniques in this study include mathematical literacy tests and digital literacy questionnaires, with data analysis using two-way ANOVA. The results indicate that 1) There is an effect of the reciprocal teaching model on students' mathematical literacy skills; 2) There is an effect of high, medium, and low levels of digital literacy on students' literacy skills; and 3) There is an interaction between the reciprocal teaching model and digital literacy on students' mathematical literacy skills. Based on these results, the implementation of reciprocal teaching learning and digital literacy in a synergistic manner can enhance students' mathematical literacy skills. This highlights the importance of integrating interactive teaching strategies and digital literacy development into the educational curriculum in the digital era.